PARTISIPASI KELOMPOK SADAR WISATA TERHADAP PENERAPAN SAPTA PESONA - Inggris, Raja; Nurwahidah, Laela; Mir'atunnisa, Rifka; Rahadian, Muhammad Reynaldi (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Regional development in tourism development programs is currently rife. One of them is in Padakembang Village, Tasikmalaya Regency, which has potential and interesting resources to be developed as a tourist destination. However, with the potential of the village, it is necessary to sensitize the local community to participate, maintain and develop it through tourism awareness groups in supporting sapta pesona to create a conducive climate for the growth and development of tourism. This research uses qualitative research methods. The research was conducted by maximizing observations conducted by means of interviews in order to get a strong expression to then be studied in depth and disclosed in this paper. The results showed that Padakembang Village has tourism potential that can be developed and has attractions that can be visited such as hot spring tourism, religious tourism and craft tourism. However, from the abundant natural potential, researchers found that in terms of facilities and infrastructure, the development of Padakembang Tourism Village still needs a lot of improvement. With strong collaboration, tourism in Padakembang Village will continue to develop in a sustainable manner so as to create a memorable and sustainable tourism experience for tourists, and improve the welfare of the local community.